Procesy decyzyjne w gospodarce przestrzennej - Szczepańska, Agnieszka (Space – Society – Economy, 2009)
Human activity is primarily oriented towards needs satisfaction. The catalogue of various needs accounts for those that relate to life in a given segment of space. Therefore, space may be viewed as a commodity that is an object of competition among several consumers. The higher the value of that commodity, i.e. space in the analyzed case, the greater the resulting conflict. Most conflicts are stirred by the limitedness of space and the unlimitedness of consumer needs. The limitedness of space is the prime motive for the competition between business entities – consumers of space who strive to gain control over the largest stretch territory for their individual needs.The main factor limiting the emergence of conflict situations is an appropriate space policy which involves the development of planning studies. Functions are attributed to a given fragment of space through the enforcement of the decisionmaking process. The main goal of spatial policies, which embody the principles of spatial management, should be to limit spatial conflict. For this reason, the achievement of spatial order is of key significance in spatial policy.The optimal method of spatial management cannot be accurately determined as absolutely optimal solutions cannot be chosen in any situation, including the planning process and spatial management. The above is affected by environmental variability, changing social needs and the inability to fully predict the future consequences of spatial management solutions. Every such measure is merely an attempt to reach spatial order and minimize spatial conflict.